Foye's principles of medicinal chemistry - Thomas L. Lemke; Roche, Victoria F.; Zito, S. William; Lemke, Thomas L.; Williams, David A., 1938- (2020)
"With expert contributions from experienced educators, research scientists and clinicians, Foye's Principles of Medicinal Chemistry, Eighth Edition is an invaluable resource for professional students, graduate students and pharmacy faculty alike . This 'gold standard' text explains the chemical basis of drug action, emphasizing the structure-activity relationships, physicochemical-pharmacokinetic properties, and metabolic profiles of the most commonly used drugs"--
Includes bibliographical references and indexes.
Keywords: Chemistry, Pharmaceutical